2022
DOI: 10.1039/d2sc04434j
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene nanoplastics affect the human ubiquitin structure and ubiquitination in cells: a high-resolution study

Abstract: A high-resolution study of ubiquitin–polystyrene nanoparticle (PS-NP) interaction is reported. We also show the effects of PS-NPs on ubiquitination in HeLa cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Adapted with permission. [230] Copyright 2022, RSC. Recent research in dandelion (Taraxacum officinale) reported alteration in the 3D conformation of Rubisco, and DHA on interaction with virgin 80 nm PSNPs, and its carboxy and amino modifications.…”
Section: Pnps Induce the Tertiary Structural Aberrations In Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adapted with permission. [230] Copyright 2022, RSC. Recent research in dandelion (Taraxacum officinale) reported alteration in the 3D conformation of Rubisco, and DHA on interaction with virgin 80 nm PSNPs, and its carboxy and amino modifications.…”
Section: Pnps Induce the Tertiary Structural Aberrations In Proteinsmentioning
confidence: 99%
“…In understanding the secondary structural transition, the CD pattern indicated the modulation in protein secondary structure; however, it defied the typical model of α helix to β sheet/random coil transition (Figure 4b). [ 121 ] Nanoplastics have also been found to bind α amylase at multiple sites at chain A involving critical amino acids Trp163, Ala42, and Leu167, which leads to PNP concentration dependent secondary structural changes in the protein. [ 122 ] A recent study reported that PNPs enhance the relative abundance of α helix and 3‐turn helix as compared to the sum of antiparallel β‐sheet and random coil.…”
Section: Molecular Insights Into Protein‐pnp Interactionsmentioning
confidence: 99%
See 1 more Smart Citation